Provision of Patient Medication Counseling Service In A Tertiary-Care Eye Hospital In Bandung: A Gap Analysis of Patient’s Need, Standard and Service Provider Resources - Hendrayana, Tomi; Zazuli, Zulfan; Fadhila, Genialita; Cahyono, Nur Sidik (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2017)
Many studies showed that counseling can improve patient adherence and reduce medication-related problems leading to reach an optimal outcome therapy. The aims of this study were to identify patient’s need, healthcare professional’s support, pharmacist’s readiness and step to be taken to meet standard for implementing patient medication counseling service. Questionnaires has been given to hospitalized-patient to identify the patient’s need and to healthcare professionals in recognizing their supports, followed by survey of pharmacist’s readiness. Gap analysis was then carried out to identify the additional resources to be provided for conducting the service. About 103 patients were enrolled and eager for drug counseling to be implemented with pharmacist as healthcare counselor. Approximately 46 nurses and 25 active-medical-doctors were participated and giving their support for pharmacist to provide the service; and pharmacists are ready to conduct patient medication counseling with minor adjustment. Gap analysis concluded that additional resources should be furnished, e.g. information module consist of standard information needed by the patient, standard operational procedure, and updated literatures. Due to lack of pharmacist, counseling service only be delivered to patient who has a complex antibiotic regimen therapy. Our data showed that patient medication counseling service in this center could be quickly implemented.